A Proof of Calibration Via Blackwell's Approachability Theorem - Dean P. Foster (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
Over the past few years many proofs of calibration have been presented (Foster and Vohra (1991, 1997), Hart (1995), Fudenberg and Levine (1995), Hart and Mas-Colell (1996)). Does the literature really need one more? Probably not, but this algorithim for being calibrated is particularly simple and doesn't require a matrix inversion. Further the proof follows directly from Blackwell's approachability theorem. For these reasons it might be useful in the class room.
Keywords: 330